IMPLEMENTASI TERAPI MINDFULNESS DALAM PENANGANAN INSECURITY PADA REMAJA: STUDI KASUS PROGRAM MITRA CITRA REMAJA PKBI CABANG CIREBON - Jubaedi, Muhamad; Subhan (Prodi Tasawuf dan Psikoterapi, Fakultas Agama Islam, Universitas Muhammadiyah Cirebon, 2024)
This research is motivated by the phenomenon of mental health both in the world and in beloved Indonesia, the problem that often arises with adolescents is mental health problems. A healthy mentality is marked by the achievement of well-being for himself, happiness that is felt by his feelings, and shown with his behavior. What causes mental health problems include the emergence of anxiety disorders, which have an impact on the emergence of feelings of insecurity or insecurity. So with the theory and knowledge that has been obtained, to handle it by means of a psychotherapeutic method approach using mindfulness therapy techniques with three stages, namely visual imagery (visual imagination), deep breathing (deep breathing), self talk (talking about accepting oneself) and do not forget the discipline of Sufism, namely muraqabah. This research was conducted at the Cirebon Branch of PKBI Youth Mitra Citra program whose target was the 'CEMPAKA' Youth Posyandu RW.02 Krucuk, Cirebon City. The results obtained from 22 respondents fulfilling the eligibility became 20 adolescent respondents and 5 MCR peer counselors. The change obtained from RW.02 youth was that from 20 respondents it was found that 15% with a large insecure scale became nil, medium as much as 10% became nil, and moderate initially 45% became 35% or as many as 7 respondents, then with a small scale level from 30% to 65% or 13 people are safer in insecure problems.